(untitled) (Research, Society and Development, 2020)
The jerivá fruit (Syagrusromanzoffiana Cham.) has a good nutritional profile, considered rich in carbohydrates, vitamins, fibers and minerals. In addition, almonds are potential sources of lipids for the production of biofuel. Considering these potentialities and the presence of this fruit in the brazilianCerrado. This study aimed to biometric characterization, physicochemical, bioactive compounds and antioxidant capacity of the pulp, and lipid content of the jerivá almond. About 5 kg of fruits were collected from three plants located in the botanical garden area of Campus Rio Verde, with a totally yellow color. After collection, they were sanitized, vacuum-packed and frozen. Evaluations of mass and size of fruits, moisture, ash, vitamin C, carotenoids and antioxidant capacity of the pulp, and lipid content of the almond were carried out. The fruits had, on average, a mass around 9 g and a longitudinal axis of approximately 30 mm, vitamin C content of 19 mg 100g-1 and antioxidant activity of 74%, by β-carotene/linoleic Acid method. The lipid content of the almonds was around 30%. This study indicated that the jerivá fruit can be defined as a functional food, due to its vitamin C content and high antioxidant capacity, besides being promising for the production of biodiesel, due to the lipid concentration of the almond.